Spatial and temporal analysis of mortality from gastric cancer in Brazil, 2001 to 2020 (Research, Society and Development, 2022)
Objective: To temporally and spatially analyze mortality from stomach cancer in Brazil and its regions from 2001 to 2020. Methodology: This is an ecological study on mortality from malignant stomach neoplasms in Brazil and its regions, in the period from 2001 to 2020. 2001 to 2020. Data came from the Mortality Information System (MIS). Mortality Rates were calculated and standardized using the direct method. A temporal trend analysis was performed using the JoinPoint technique. Spatial analysis was performed using the Moran Global and Local Index. Results: In Brazil, 171,464 deaths from gastric cancer were recorded, in males with an average Standardized Mortality Rate (SMR) of 16.72 deaths per 100,000 males. The temporal trend, in males, was of decline in Brazil (Average Annual Percent Change - AAPC= -2.4% and in females -1.8% (p0.05) and in the Northeast there was an increase (AAPC=0.8%). Regions such as the Southeast and South and part of the Northeast (Ceará) presented spatial clusters with high mortality rates in both sexes. Conclusion: The temporal trend showed that standardized mortality rates are on a slope in Brazil, in the South, Southeast regions and Central-West, while it was stable in the North and an increase in the Northeast. Cities in the Southeast and South and part of the Northeast showed clusters with high rates.